Zhen-Wu decoction and lactiflorin, an ingredient predicted by in silico modelling, alleviate uremia induced cardiac endothelial injury via Nrf2 activation. (15th November 2022) - Liu, Xin; Li, Yue; Ni, Shi-Hao; Sun, Shu-Ning; Deng, Jian-Ping; Ou-Yang, Xiao-Lu; Huang, Yu-Sheng; Li, Huan; Chen, Zi-Xin; Feng, Wen-Jun; Lian, Zhi-Ming; Wang, Zhen-Kui; et al.
Abstract: Ethnopharmacological relevance: Cardiorenal syndrome type 4 (CRS type 4), with high rates of morbidity and mortality, has become a social and economic problem worldwide over the last few decades. Zhen-Wu decoction, a traditional medicine used in East Asia, has been widely used in the treatment of cardiovascular disease and kidney disease, and has shown potential therapeutic effects for the clinical treatment of CRS type 4. However, the underlying mechanism has not been extensively explored. Aim of the study: The purpose of this study was to investigate the effect and underlying mechanism of Zhen-Wu decoction on uremic cardiomyopathy, offering a potential target for clinical treatment of CRS type 4. Materials and methods: Five/six nephrectomized mice were utilized for experiments in vivo. The cardioprotective effects of Zhen-Wu decoction were evaluated by echocardiography and tissue staining. RNA-Seq data were used to investigate the potential pharmacological mechanism. The prediction of targets and active components was based on our previous strategy. Subsequently, the protective effect of the selected compound was verified in experiments in vitro. Results: Zhen-Wu decoction alleviated cardiac dysfunction and endothelial injury in 5/6 nephrectomized mice, and the mechanism may involve the inflammatory process and oxidative stress. The activation of the Nrf2 signaling pathway was predicted to be a potential target of Zhen-Wu decoction in protecting endothelial cells. Through our machine learning strategy, we found that lactiflorin as an ingredient in Zhen-Wu decoction, alleviates IS-induced endothelial cell injury by blocking Keap1 and activating Nrf2. Conclusions: The present study demonstrated that Zhen-Wu decoction and lactiflorin could protect endothelial cells against oxidative stress in mice after nephrectomy by activating the Nrf2 signaling pathway. Graphical abstract: Image 1